Power and muscular endurance repeatability with 48 hours rest - Hammond, K.; Schilling, B. K.; Weber, A. A.; Bloomer, R. J.; Weiss, L. W.; Ferreira, L. C. (The Journal of Strength and Conditioning Research, 2010)
Athletes often perform intense workouts with short intervals between sessions. The purpose of this investigation was to examine the ability to repeat a high volume chest press workout following a 48 hour rest interval between sessions, as part of a larger intervention. 15 resistance trained men (age 26 +/- 4) were recruited from the university population. Subjects performed a one-repetition maximum (1RM) in the bench press exercise on a machine device that allowed independent movement of each arm (Hammer Strength(TM)). Two to four minutes of rest was given between attempts. The highest load lifted in good form was recorded as their 1RM. The following week subjects reported to the lab for two testing sessions 48 hours apart. Power testing was measured by performing bench press throws (BPT) using a weight equivalent to 30% of predetermined machine 1-RM using a ProSpot(R) device. This apparatus utilizes a self spotting mechanism that contains an electronic sensor, allowing the subject to release the bar at the end range of motion, ensuring a ballistic measure. The subjects laid on a flat bench placed on a uniaxial force plate (Roughdeck) and a position transducer was tethered to the center of the ProSpot(R) barbell. The first derivative of position with respect to time was taken to calculate velocity of the barbell (Datapak5) and multiplied by force to calculate power (Watts). Data was sampled at 1000Hz and low-pass filtered with a cutoff frequency of 30 Hz. Three BPTs were performed with 90 seconds rest between each effort. The best power output of the 3 BPTs was recorded. Subjects were then given 10 minutes of rest before performing 10 sets of the bench press exercise using a load equal to 60% of 1RM. Each set was performed to a point of momentary muscular failure, using a controlled speed. Subjects were given 90 seconds of rest between each set. No significant differences were observed in power output, 1st set repetitions, total repetitions, mean reps, or volume load from day 1 to day 2 (see table). Although not statistically significant, bench press power was decreased from day 1 to day 2 of testing (2.3%), while bench press endurance measures were slightly increased from day 1 to day 2 of testing (3.2% total reps, 3.6% total volume load). A 48 hour rest interval is sufficient for recovery of power and repeatability of muscular endurance workouts in resistance trained men. Further research is needed to examine the repeatability of shorter or longer rest intervals between workouts. Coaches can design periodized training programs that allow for high-volume muscle group training sessions to be repeated at 48 hours at certain times of the training cycle.